Investigating EFL learners’ beliefs about The use of academic writing strategies. Case study: third year students at the Department of English–M’sila University - Ibtissame RAHMANI, Khawla DJAIDJAA (UNIVERSITY OF MOHAMED BOUDIAF, 2021)
ABSTRACT The present study aims to explore learner’s beliefs towards academic writing strategies to see the impact and relationship of learners’ beliefs and academic writing strategies on academic writing. To achieve the objectives of the study, a mixed method (quantitative and qualitative) was used. A survey questionnaire served as the main data-gathering tool in this research. Sixty third year EFL students were used as the main sample of the study which took place at the level of the English Department at M’sila University. The obtained results show that third year students do have strong beliefs which impact on their use of academic writing strategies both positively and negatively, which made them face different difficulties in relation to academic writing process. For instance, EFL learners think that they should not do any sort of writing as assignments unless they get well prepared.
Keywords: Key words: academic. writing. strategies